Advancing Equity, Diversity, and Inclusion in Data Research: Insights from a PEDRI Cross-Sector Roundtable - Khan, Samaira; Tembo, Doreen; Porter, Katie; Smith, Cassie (International Journal of Population Data Science, 2026)
Persistent inequities in research datasets mean that marginalised communities are routinely under-represented. Engagement practices often unintentionally exclude the very groups most affected by data-driven decisions, while organisations frequently lack the training, resources, or guidance needed to address these gaps. Together, these issues risk reinforcing structural inequities and undermining the quality, relevance, and public trust of data research. To respond to these challenges, PEDRI convened a cross-sector roundtable in September 2025, bringing together twenty researchers, engagement practitioners, inclusion specialists, and public contributors to identify practical strategies for embedding EDI throughout the research lifecycle. Participants identified several critical barriers: exclusionary engagement practices, over-reliance on the same communities, inconsistent data collection standards, lack of funding for Public Involvement and engagement and insufficient EDI training for researchers and data managers. The group identified a range of solutions rooted in intersectional approaches and the need to embed meaningful public involvement at every research stage. Priority actions included expanding PEDRI’s Resources Hub with tailored EDI guidance, strengthening its convening role, and working with partners across the sector nationally and internationally to connect researchers with diverse communities, reduce engagement burden, and align sector-wide EDI and PIE priorities. This presentation will share concrete findings, cross-sector solutions, and priority actions arising from the roundtable. By placing inclusion at the heart of data research, we can build not only better datasets, but a fairer, more trustworthy research ecosystem that serves all communities.